1995
DOI: 10.1007/bf02788967
|View full text |Cite
|
Sign up to set email alerts
|

Study of distribution and interaction of arsenic and selenium in rat thyroid

Abstract: Seventy-eight Wistar weanling rats were pretreated with arsenate (100 mg/L As), selenite (1 mg/L Se), and arsenate (100 mg/L As) plus selenite (1 mg/L Se) added to the drinking water. After 4 w, all the animals were sacrificed and serum T3 and T4 were determined by double-antibody radioimmunoassay. Thyroid tissue concentrations of As and Se were determined in female rats by neutron activation analysis, and tissue specimens were examined histopathologically. For both sexes, the measurements indicated that T4/T3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Selenium in turn facilitated the biliary excretion of arsenic. Glattre et al studied the distribution and interaction of arsenic and selenium in rat thyroid and suggested that both arsenic and selenium accumulate in thyroid tissue 119) . Toxic changes were seen during post mortem examination, whereas only minor changes were observed in the selenium or arsenic plus selenium treated groups.…”
Section: Seleniummentioning
confidence: 99%
“…Selenium in turn facilitated the biliary excretion of arsenic. Glattre et al studied the distribution and interaction of arsenic and selenium in rat thyroid and suggested that both arsenic and selenium accumulate in thyroid tissue 119) . Toxic changes were seen during post mortem examination, whereas only minor changes were observed in the selenium or arsenic plus selenium treated groups.…”
Section: Seleniummentioning
confidence: 99%
“…Inorganic arsenic has been shown to modify metabolism of selenium and influence the anti-carcinogenic activity of inorganic and organic selenium compounds 23,24 . Some data also demonstrate that pre-or co-exposure to inorganic selenium exerts protective effect against toxicity of arsenic [25][26][27] . In our study the level of arsenic cumulation in the thyroid was not significantly influenced by dietary selenium supplementation.…”
Section: Discussionmentioning
confidence: 94%
“…In 1995 we published a study (14) of the distribution and interaction of arsenic and selenium in the rat thyroid. This was meant as supplement to previous selenium studies, and was based on one of the subhypotheses that can be deduced from the seafood hypothesis: Seafood has been the main human source of arsenic in the second half of the twentieth century.…”
Section: The Experimental Armmentioning
confidence: 99%
“…• The thyroid gland as target tissue for selenium, arsenic and tellurium (neighbors in the periodic system) (14,27). …”
Section: Selected Achievementsmentioning
confidence: 99%